Control of the transition to long-term nonprogressor in tristable HIV dynamics. - Chang,H; Astolfi,A (Annu Int Conf IEEE Eng Med Biol Soc, 2008)
The human immunodeficiency virus (HIV) infection, that causes acquired immune deficiency syndrome (AIDS), is a dynamic process that can be modeled via differential equations. In this paper we apply a control strategy to boost the immune response for a tristable HIV dynamic model. The purpose of this control method is to steer the system to an equilibrium condition known as long-term nonprogressor, which corresponds to an infected patient that does not develop the symptoms of AIDS. The control strategy is implemented by controlled drug scheduling based on the understanding of the immune boosting mechanism. The feasibility of the methodology is illustrated via simulations.